Hydrodynamik in Hochdruckblasensäulen. Issue 7 (11th April 2013) - Rollbusch, Philipp; Tuinier, Martin; Becker, Marc; Ludwig, Martina; Grünewald, Marcus; Franke, Robert; Grünewald, Marcus; Lausch, Hans‐Rolf; Schlüter, Michael
<x xml:space="preserve">Abstract</x> Bubble column hydrodynamics influence important performance parameters like conversion, selectivity and yield of a chemical reaction. Backmixing of the liquid phase and gas holdup are thereby of particular importance. In order to determine these parameters, a number of correlations exist within the literature. These correlations are mainly derived from small scale equipment operated at atmospheric conditions by the use of the physical system air/water. Published experimental results regarding gas holdups and dispersion in bubble columns operated under high pressure are discussed and a recommendation for further research is given.